Papulopustular Dermatitis in X-Linked Chronic Granulomatous Disease - Rajani, Puja Sood; Slack, Maria A. (Frontiers in Pediatrics, 2019)
Abstract: Here we describe two term male infants diagnosed with X-linked CGD who present, in addition to frequent infection, with a unique papulopustular skin rash. CGD is caused by a number of genetic defects that impair phagocyte function. This disease results in recurrent infections and granuloma formation. Rarely do patients develop cutaneous symptoms, unless associated with autoimmune disorders such as systemic erythematous lupus (Agarwal, 2015). Each male infant mentioned here was diagnosed with CGD based on abnormal DHR testing and confirmatory genetic testing. The presenting papulopustular dermatitis was initially characterized as non-classic appearing eczema and subsequently found to be refractory to usual eczema treatment and antibiotics. After obtaining written informed consent from both families, we have documented photographs of the development of a characteristic rash in two newly diagnosed infants with CGD. One infant underwent cutaneous biopsy with histologic evaluation and negative cultures. The dermatitis for both infants was refractory to topical and systemic therapies, and resolved after bone marrow transplantation. Our objective was to characterize cutaneous findings in X-linked CGD and emphasize the importance of considering further immune workup in patients who present with unusual cutaneous findings that do not fit with common infant rashes in conjunction with concerning features for primary immunodeficiency.